Image feature extraction by dynamic neural filtering and phase-only joint transform correlation - Bal, Abdullah (ELSEVIER SCI LTD, 2007)
Neural network-based image processing algorithms present numerous advantages due to their supervised adjustable properties. Among various neural network architectures, dynamic neural networks, Hopfield and Cellular networks, have been found inherently suitable for filtering applications. Combining supervised and filtering features of dynamic neural networks, this paper presents dynamic neural filtering technique based on Hopfield neural network architecture. The filtering technique has also been implemented by using phase-only joint transform correlation (POJTC) for optical image processing applications. Filtering structure is basically similar to the Hoplield neural network structure except for the adjustable filter mask and 2D convolution operation instead of weight matrix operations. The dynamic neural filtering architecture has learnable properties by back-propagation learning algorithm. POJTC presents significant advantages to achieve the operation of summing the cross-correlation of bipolar data by phase-encoding bipolar data in parallel. The image feature extraction performance of the proposed optical system is reported for various image processing applications using a simulation program. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: image feature extraction; dynamic neural network; phase-only joint transform correlator; OPTOELECTRONIC IMPLEMENTATION; LEARNING ALGORITHM; NETWORK; SEGMENTATION; CLASSIFICATION; Optics; Physics